2001
DOI: 10.1080/019262301753178474
|View full text |Cite
|
Sign up to set email alerts
|

The Tg.AC (v-Ha-ras) Transgenic Mouse: Nature of the Model

Abstract: The Tg.AC (v-Ha-ras) transgenic mouse model provides a reporter phenotype of skin papillomas in response to either genotoxic or nongenotoxic carcinogens. In common with the conventional bioassay, the Tg.AC model responds to known human carcinogens and does not respond to noncarcinogens. It also does not respond to most chemicals that are positive in conventional bioassays principally at sites of high spontaneous tumor incidence. The mechanism of response of the Tg.AC model is related to the structure and genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…The International Life Sciences Institute (ILSI) sponsored a collaborative evaluation program to examine alternative models for carcinogenicity testing (Cohen et al, 2001;Robinson and MacDonald, 2001;Tennant et al, 2001). With the ILSI initiative and individual lab testing, a wide variety of chemicals have been tested on Tg.AC mice in an effort to validate the model Spalding et al, 1999Spalding et al, , 2000.…”
Section: Tgac and Chemical Carcinogenesismentioning
confidence: 99%
“…The International Life Sciences Institute (ILSI) sponsored a collaborative evaluation program to examine alternative models for carcinogenicity testing (Cohen et al, 2001;Robinson and MacDonald, 2001;Tennant et al, 2001). With the ILSI initiative and individual lab testing, a wide variety of chemicals have been tested on Tg.AC mice in an effort to validate the model Spalding et al, 1999Spalding et al, , 2000.…”
Section: Tgac and Chemical Carcinogenesismentioning
confidence: 99%
“…This is primarily because the Tg.AC mouse traditionally has been used in studies involving dermal application of a test chemical with subsequent enumeration of skin tumors only (Eastin et al, 2001;Tennant et al, 2001). Only one NIEHS study reported on tumor types other than skin (Tokar et al, 2010).…”
Section: Background Tumor Incidencesmentioning
confidence: 99%
“…Nonetheless, specific and consistent housing and husbandry practices can effectively prevent false positive papillomas albeit at some additional cost per mouse (26). Spontaneous skin papilloma incidence in untreated or negative control groups of singlehoused mice has been reported to be less than 4% (26,35,69). The utility of the Tg.AC mouse, however, may be restricted to topical application of suspect carcinogens as oral gavage of chloroform failed to activate the v-H-ras transgene in the liver of treated mice (11).…”
Section: History Of the 2-year Rodent Bioassaymentioning
confidence: 99%
“…The Tg.AC mouse contains multiple copies of an activated form of the ras oncogene (31,69). The Tg.AC mouse is sensitive to skin papillomas and squamous cell carcinomas in response to topical application of skin tumor promoters, 355 TOXICOLOGIC PATHOLOGY presumably because the initiating mutation in Ha-ras has been provided by the v-H-ras transgene (3,64).…”
Section: History Of the 2-year Rodent Bioassaymentioning
confidence: 99%